Factors Influencing Customer’s Satisfaction towards Broadband Services - Li, Dawei; Wong, Chee Hoo; Lim, Kim Yew; Ng, Alex, Hou Hong (INTI International University, 2019)
This study examined the factors that influenced the satisfaction of broadband services among service providers of broadband in Beijing, China. There is limited research literature on customer satisfaction with broadband in China. This is also the gap due to the limited literature on customer satisfaction and broadband in China. From the above information analysis, it is necessary to research this subject. The focus of this research was on major factors towards customer satisfaction with broadband in China. This research used primary data and individuals as the unit of analysis to answer the research objectives. 395 completed questionnaires were collected from the samples located in Beijing. Data were further analyzed and the hypotheses were tested using Multiple Regression Analysis under SPSS. The finding of the research had demonstrated that all hypotheses namely price, perceived quality, brand awareness and customer service were significant in influencing the satisfaction of broadband service in China. This study found out that the most important impact on customer satisfaction came from customer service. The regression equation model was also proposed at the end of the study. The findings provide some contributions to the academicians and practitioners alike.